2002
DOI: 10.1093/emboj/cdf361
|View full text |Cite
|
Sign up to set email alerts
|

Growth factors can activate ATF2 via a two-step mechanism: phosphorylation of Thr71 through the Ras-MEK-ERK pathway and of Thr69 through RalGDS-Src-p38

Abstract: Transcription factor ATF2 regulates gene expression in response to environmental changes. Upon exposure to cellular stresses, the mitogen-activated proteinkinase (MAPK) cascades including SAPK/JNK and p38 can enhance ATF2's transactivating function through phosphorylation of Thr69 and Thr71. However, the mechanism of ATF2 activation by growth factors that are poor activators of JNK and p38 is still elusive. Here, we show that in ®broblasts, insulin, epidermal growth factor (EGF) and serum activate ATF2 via a s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
191
1
5

Year Published

2004
2004
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 204 publications
(205 citation statements)
references
References 67 publications
8
191
1
5
Order By: Relevance
“…1A, upper two panels) in short TOP and FOP; the ␤-catenin Ser 33 (␤-cat S33) construct containing full-length ␤-catenin with a mutation at Ser 33 and its corresponding empty vector control, pcDNA3Zeo⌬MCS, in short pcDNA3Zeo (14); the 5ϫjun2 TATA pGL3, in short 5ϫjun, 5ϫcollTRE TATA pGL3, in short 5ϫcoll, TATA pGL3 (15,16) (Fig. 4A, upper panel), Ϫ1600/ϩ740 wt c-jun TATA pGL3, and Ϫ1600/ϩ740 m1 ϩ 2 c-jun TATA pGL3, luciferase reporter constructs (17); the Myc-tagged cdc42 V12 construct, encoding constitutively active Cdc42, and its corresponding empty vector control, pMT2 (18); and the HA-tagged ATF2 construct, HA-ATF2 (19). The p-AP-1-Luc or 7ϫAP-1 reporter construct (Stratagene, Cedar Creek, TX) was a kind gift from M. Karperien (Leiden University Medical Center, Department of Endocrinology, Leiden, The Netherlands).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…1A, upper two panels) in short TOP and FOP; the ␤-catenin Ser 33 (␤-cat S33) construct containing full-length ␤-catenin with a mutation at Ser 33 and its corresponding empty vector control, pcDNA3Zeo⌬MCS, in short pcDNA3Zeo (14); the 5ϫjun2 TATA pGL3, in short 5ϫjun, 5ϫcollTRE TATA pGL3, in short 5ϫcoll, TATA pGL3 (15,16) (Fig. 4A, upper panel), Ϫ1600/ϩ740 wt c-jun TATA pGL3, and Ϫ1600/ϩ740 m1 ϩ 2 c-jun TATA pGL3, luciferase reporter constructs (17); the Myc-tagged cdc42 V12 construct, encoding constitutively active Cdc42, and its corresponding empty vector control, pMT2 (18); and the HA-tagged ATF2 construct, HA-ATF2 (19). The p-AP-1-Luc or 7ϫAP-1 reporter construct (Stratagene, Cedar Creek, TX) was a kind gift from M. Karperien (Leiden University Medical Center, Department of Endocrinology, Leiden, The Netherlands).…”
Section: Methodsmentioning
confidence: 99%
“…4A, upper panel). The 5ϫcoll and 7ϫAP-1 reporters are activated by Jun-Fos heterodimers and can be strongly induced by TPA (19,27). The 5ϫjun reporter construct mainly monitors Jun-ATF activity and is hardly enhanced by TPA.…”
Section: Membrane-targeted Mouse C-terminal Polycystin-1 Does Not Augmentioning
confidence: 99%
See 1 more Smart Citation
“…Activation of ATF-2 by p38/JNK is thought to play a role in apoptosis (Gupta et al, 1995). ATF-2 is also activated by insulin, epidermal growth factor, and serum via a two-step mechanism involving two distinct Ras effector pathways (Ouwens et al, 2002). A group of ATF-2 target genes have been identified that are involved in multiple biological phenomena.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, Rta activates the BZLF1 promoter through an ATF2 site in the ZII region (Adamson et al, 2000). Therefore, activation of the ERK signal transduction pathway by Rta may ultimately influence the transcription of BZLF1 through the activation of ATF2, a downstream target of the ERK signal transduction pathway (Morton et al, 2004;Ouwens et al, 2002). The first piece of evidence in support of this hypothesis is the fact that the binding capacity of GST-BRAP2-glutathione-Sepharose beads to KSR1 declined substantially when the beads were pre-incubated with cell lysates containing Rta (Fig.…”
Section: Discussionmentioning
confidence: 99%